2016
DOI: 10.15561/18189172.2016.0402
|View full text |Cite
|
Sign up to set email alerts
|

Tests and standards for express-control of physical fitness and health of middle school age pupils

Abstract: Abstract. Introduction: to day, physical fitness testing often causes negative emotions in pupils. It results in sharp loss of pupils' wish to fulfill physical exercises in free time and worsens their health. Possibility to assess health level is an important motivation factor for pupils' passing physical tests. Objective testing system will form positive motivation for physical exercises' practicing and will facilitate increase of pupils' motor functioning. It will also facilitate optimization of their physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Results of cluster analysis were used for working out approximate academic requirements of PF, considering sex and PCn indicators of senior pupils: body length, relative body mass and CC. Their information potential was substantiated by us at previous stages of the research [19][20][21]. Limits of average level of pupils' competence were Х±σ, sufficient and low -from Х±σ to Х±2σ, high -above Х±2σ.…”
Section: Body Length Body Massmentioning
confidence: 68%
See 1 more Smart Citation
“…Results of cluster analysis were used for working out approximate academic requirements of PF, considering sex and PCn indicators of senior pupils: body length, relative body mass and CC. Their information potential was substantiated by us at previous stages of the research [19][20][21]. Limits of average level of pupils' competence were Х±σ, sufficient and low -from Х±σ to Х±2σ, high -above Х±2σ.…”
Section: Body Length Body Massmentioning
confidence: 68%
“… Authors' methodic of assessment of pupils' motor fitness, which combine commonly known control exercises in different variants [7,8];  Diagnostic system for children's psycho-motor readiness for studying at school [19];  Individual requirements to junior pupils' PF [9];  Normative system for PF and health express control of secondary school age pupils [20].  Objective criteria for determination of secondary school age pupils' functional reserves [21].…”
mentioning
confidence: 99%
“…An important element in coordination abilities development is the availability of informative pedagogical control indicators (Krutsevych, Vorobiov & Bezverkhnia, 2011;Ivashchenko & Kapkan, 2016;Bodnar & Andres, 2016) and the knowledge of peculiarities of teaching methods (Liakh, 2000;Khudolii, 2008;Ivashchenko, 2016). The methodology of pedagogical control applies multidimensional mathematical and statistical methods of analysis (Lopatiev, Ivashchenko, Khudolii, Pjanylo, Chernenko & Yermakova, 2017;Ivashchenko, Khudolii, Iermakov, Prykhodkon & Cieslicka, 2018).…”
mentioning
confidence: 99%
“…In other studies it was shown that intensive physical loads strengthen students' health and facilitate their academic progress [17,34,46]. In application of such trainings it should be remembered that there is deficit of operative, reliable and informative methodic for control and assessment of loads intensity at physical culture lessons [7,25].…”
mentioning
confidence: 99%